Writing Techniques in the English Love and Lyric Poems - Assist. Lect. Ghaith Saleh Mahdi; Ali Abbas Jasim Mohammed; Mahmood Shaalan Atiyah Alsalmani (Genius Journals, 2022)
In the poetry creation, poets use many different writing techniques. This paper expounds the image expressions in British love poems and lyrics from four aspects: description, symbolism, figure of speech and personification. Man has been singing for love since written language was invented. Love has been the eternal subject theme of poems and become perpetual singing. Many poets also worship nature and sing for nature. In order to express their feelings and emotions, poets at all times and in all countries pay much attention to using image expressions and creation in their poems. There are no poems without images. Words are carriers of images. Although poets are in different times, they have the similar writing techniques, we can still find the same or similar image expressions from different poems of different poets. This paper will analyze image expressions in British love poems and lyrical poems from four aspects --- description, symbolism, figure of speech and personification.
Keywords: Poet; Image expressing; Love